IMPLEMENTATION OF PROSOCIAL EDUCATION THROUGH EXPERIENTIAL LEARNING IN THE SUBJECT OF KEMUHAMMADIYAHAN - Ilham Mundzir (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
Prosocial education is an educational program to increase motivation and skills of the student to help, care for others in need. This article is aimed at analyzing the implementation of prosocial education in the Kemuhammadiyahan subject. Using experiential learning method, students not only learn about Muhammadiyah from an organizational, historical and ideological perspective, but also experience and practice al-Ma'un theology in carrying out da'wah empowerment of the duafa family. This research design was a descriptive qualitative. The data were collected by making observations during the activity, interview, and documentary studies. Using content analysis, this study found that this da'wah for empowerment of the duafa family was in line with the objectives of prosocial education, namely increasing empathy and concern for the mustad'afin group